Penerapan Metode Weight Product (WP) untuk Rekomendasi Pemilihan Jasa Paket Laundry Terbaik - Rima Tamara Aldisa; Rifando Adeyansa Purba (Journal of Information System Research (JOSH), 2023)
Laundy is an activity of washing clothes or the like at the same time and place in one place. The author takes samples to select package services from one of the shops or laundry businesses, namely dry regular, dry medium and dry express which customers can choose from with differences in turnaround time, weight and price, and can help laundry shop owners find out the type of packages that are often chosen by customers and can make it easier for shop owners to find out the results of sales transactions and reports. To understand this, we need a recommendation system that can help customers and laundry shop owners according to what the author wants. Here the author uses the Product Weight method to find alternative values ​​or the best results using several calculation formulas and gets a result of 0.335 on R2, namely Dry Medium with price criteria, completion time and weight